Pharmacokinetic variability of valproate in women of childbearing age. (22nd August 2017) - Johannessen Landmark, Cecilie; Burns, Margrete Larsen; Baftiu, Arton; Farmen, Anette Huuse; Lossius, Morten I.; Johannessen, Svein I.; Tomson, Torbjörn
Summary: The purpose was to investigate pharmacokinetic variability of valproic acid (VPA) in women of childbearing age by therapeutic drug monitoring (TDM) data to elucidate the variable relationship between dose and serum concentrations with the ultimate aim of facilitating safer use of VPA. Anonymized retrospective data from the TDM database (2006–2015) at the National Center for Epilepsy in Norway were used. Trough total concentrations of VPA at assumed steady state in women aged 14–46 years were analyzed. Data from 643 nonpregnant women of childbearing age (mean age = 27 years) were included. Mean dose and serum concentration of VPA were 968 (standard deviation [SD] = 453) mg/day and 411 (SD = 138) μmol/L, respectively, and 59% used polytherapy. The pharmacokinetic variability in serum concentration/dose (C/D) ratios between women was extensive. For doses <700 mg/day (n = 202; 32%; 150–625 mg/day), mean serum concentration was 336 μmol/L and variability in C/D ratio was 10‐fold. The variability decreased with increasing dose to eightfold (≥700 to <1, 500 mg/day, n = 358) and fourfold (≥1, 500 mg/day, n = 96). This study demonstrates the extensive pharmacokinetic variability of VPA among women of childbearing age, which is most pronounced at low doses. In future studies, serum concentrations of VPA, rather than dosage, should be used as a guide for exposure of VPA and possible risks of teratogenicity to evaluate safety aspects of VPA in women.